ETNOBOTANI MASYARAKAT SUKU BUNAQ (Studi Kasus di Desa Dirun, Kecamatan Lamaknen Kabupaten Belu, Provinsi Nusa Tenggara Timur) - Agustina Roswita Atok; Agus Hikmat; Ervizal A.M. Zuhud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
This study is aimed to understand and explore traditional knowledge of Bunaq ethnic in using plants The result of this study hopefully can be information material to the development, utilization and preservation of useful plants sustainably and based on local wisdom. The utilization of biodiversity at Dirun Village can be classified into 12 groups of utilization. The local people use 41 species of plants for food, 69 species for medicinal purpose, 43 species for cattle feeding, 33 species for building materials, 10 species for firewood, 20 species for plaited materials and handicraft, 7 species for toxic, 5 species for colouring materials, 5 species for tannin, 17 species for aromatic purpose, 21 species for ornamental plants, 5 species for cultural purpose and 8 species for other utilization. The local people of Bunaq ethnic have close relation to culture and nature regarding on recognizing, classifying and using the plants surround them. The utilization of plants is not for economical purpose only but for spiritual purpose also. The utilization for spiritual purpose is aimed to keep balance of the natural recourses. Keywords: traditional people, local wisdom, Bunaq ethnic.